To simplify the expression \( \frac{8}{8^{2/3}} \), we can use the properties of exponents.
First, we rewrite the numerator and the denominator:
- The numerator is \( 8 \), which can be written as \( 8^1 \).
- The denominator is \( 8^{2/3} \).
Now we can rewrite the expression as:
\[ \frac{8^1}{8^{2/3}} = 8^{1 - 2/3} \]
To simplify the exponent:
\[ 1 - \frac{2}{3} = \frac{3}{3} - \frac{2}{3} = \frac{1}{3} \]
Thus, we have:
\[ 8^{1 - 2/3} = 8^{1/3} \]
Now, \( 8^{1/3} \) represents the cube root of 8:
\[ 8^{1/3} = \sqrt[3]{8} = 2 \]
Therefore, the simplified expression is:
\[ \boxed{2} \]